2020
DOI: 10.1111/dth.13435
|View full text |Cite
|
Sign up to set email alerts
|

SB5 adalimumab biosimilar in the treatment of psoriasis and psoriatic arthritis

Abstract: Biosimilar therapies are an emerging option in the treatment of psoriasis and other immune-mediated diseases due to the lower impact on public health costs. 1,2 SB5, commercially known as Imraldi (Samsung Bioepsis), is approved in Europe for the treatment of the same clinical indications of the reference adalimumab (Humira-AbbVie). Phase III trials in rheu

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 7 publications
1
11
2
Order By: Relevance
“…PsA patients showed a significant increase in patientreported outcomes (PtGA, VAS pain and HAQ), in the DAPSA and also presented with a slight non-statistically significant increase in NSAIDs or CCS intake at 3 months. As seen for RA patients, these changes in the concomitant medications allowed the control of disease activity, with 6 months [19]. Moreover, we also presented data of clinician-reported outcomes, peripheral and overall disease activities, proving further data on real-life switching from ADA to SB5 in PsA.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…PsA patients showed a significant increase in patientreported outcomes (PtGA, VAS pain and HAQ), in the DAPSA and also presented with a slight non-statistically significant increase in NSAIDs or CCS intake at 3 months. As seen for RA patients, these changes in the concomitant medications allowed the control of disease activity, with 6 months [19]. Moreover, we also presented data of clinician-reported outcomes, peripheral and overall disease activities, proving further data on real-life switching from ADA to SB5 in PsA.…”
Section: Discussionsupporting
confidence: 59%
“…A small cohort of real-life PsA patients was recently published, showing signs of axial disease flare in 3/12 patients after switching from ADA to SB5, leading to change in concomitant medication in 2 cases and back-switch to ADA originator in the third [19]. With the exclusion of this report, no other data on ADA/SB5 switching are available for non-RA patients affected by other inflammatory RMDs.…”
Section: Introductionmentioning
confidence: 99%
“…The greater potency of these new drugs as compared to the traditional systemic agents for example, methotrexate, acitretin and cyclosporine, etc. highlights the significance of IL‐23 in the amplification of the immune response and has supported the role of Th17 cell type as the most dominant T cell subset in psoriasis 17‐21 …”
Section: Introductionmentioning
confidence: 89%
“…highlights the significance of IL-23 in the amplification of the immune response and has supported the role of Th17 cell type as the most dominant T cell subset in psoriasis. [17][18][19][20][21] Naive T-cells upon activation transform into Th1, Th2, Th17, and T regulatory cells. Each of these subsets in turn produces certain cytokines and lymphokines like Interferon-gamma (IFN-γ), TNF-α, and TNF-β.…”
mentioning
confidence: 99%
“…Safety data from real-world practice are available only for SB5. Di Cesare et al 46 reported a small cohort study of real-life PsO/PsA patients switching from reference adalimumab to SB5. Of 20 switched patients, two experienced loss of efficacy on cutaneous symptoms, with one case leading to SB5 discontinuation and switching to an IL-12/23 antagonist and the other case developing pustular psoriasis.…”
Section: Interchangeability With Reference Adalimumabmentioning
confidence: 99%